Forming Consensus To Advance Urobiome Research - Linda Brubaker (American Society for Microbiology, 2021)
Urobiome research has the potential to advance the understanding of a wide range of diseases, including lower urinary tract symptoms and kidney disease. Many scientific areas have benefited from early research method consensus to facilitate the greater, common good.